2016
DOI: 10.1080/01635581.2016.1192205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pomegranate Hull Extract on Liver Neoplastic Changes in Rats: More than an Antioxidant

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer and the third leading cause of cancer-related mortality worldwide. The current work was designed to elucidate the molecular mechanisms underlying the antitumorigenic effect of pomegranate hull extract (PHE) in livers of rats exposed to the hepatocarcinogen diethyl nitrosamine (DENA) with emphasis on oxidative stress, proliferation, and apoptosis. Male albino rats were divided into three groups: normal control, DENA group, and PHE group. PHE was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“… 46 In addition, ROS can activate various signal transduction pathways within cells, including those controlled by NF-kB, Wnt/β-catenin, PI3K, p53, and MAPK which can augment angiogenesis, promote proliferation and halt apoptosis. 47 …”
Section: Discussionmentioning
confidence: 99%
“… 46 In addition, ROS can activate various signal transduction pathways within cells, including those controlled by NF-kB, Wnt/β-catenin, PI3K, p53, and MAPK which can augment angiogenesis, promote proliferation and halt apoptosis. 47 …”
Section: Discussionmentioning
confidence: 99%
“…The parenteral or oral exposure to small quantities of NDEA results in liver damage and eventually hepatocarcinogenesis which corresponds to human HCC ( El-Ashmawy et al, 2016 ; El-Ashmawy et al, 2017 ). In the present study, the NDEA group showed enlarged livers with a greater liver index indicating that NDEA increased the proliferation of hepatic cells supported by the increase in the necroinflammation score, the upregulation of Ki-67 mRNA expression, and AFP level.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies on pomegranate have revealed its antineoplastic effect [ 20 , 21 , 22 ]. Patients treated with CDDP alone or in combination with other chemotherapeutic drugs may be exposed to serious adverse effects [ 4 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%